Certification programme for production of virus-free propagating material of grapevine and its results in Hungary - Lázár, J.; Mikulás, J.; Farkas, G.; Kölber, M. (International Journal of Horticultural Science, 2002)
In Hungary, detection of virus and virus-like diseases of grapevine began in 1960's at the Research Institute for Viticulture and Enology by János Lehoczky and his colleagues. At present, sixteen virus and virus-like diseases of Vitis vinifera are known to occur in Hungary.Regular virological screening of grapevine varieties started in 1972. The present system of screening (visual selection, indexing, ELISA) has been established using methods with continuous improvement according to recommendations of international organizations.In the first year symptomless grapevine plants are selected and marked during surveys carried out twice in the vegetation period: at about flowering and in the second half of September. At the first selection time plants are sampled for ELISA.In the spring of the second year, overwintered canes are checked by woody indexing on 8 indicator species in the field.In the third and fourth years the nursery is evaluated twice again. At the end, the marked grapevine plants, giving negative results on all indicators in every case, are considered virus-free.In autumn of the fourth year, the virus-free material is planted out under screenhouse and also in a special mother block (nuclear stock) for maintenance and propagation.Mother blocks of virus-free scion varieties have been established on 2 ha and those of rootstock varieties on 0.5 ha planted with the following number of varieties included in the national list: 71 European scion — and 12 rootstock varieties or variety candidates/clones. It is necessary to increase the area of Pre-base, Base and Certified stocks exclusively with tested virus-free (clean) material.